Assessment of the skin barrier function in the reconstructed human epidermis using a multimodal approach at molecular, tissue and functional levels. Issue 14 (28th June 2021) - Bakar, Joudi; Michael-Jubeli, Rime; El Khoury, Rindala; Hamla, Sabrina; Assi, Ali; Baillet-Guffroy, Arlette; Tfayli, Ali
Abstract : Reconstructed human epidermis models are used as epidermis alternatives in skin research studies. Abstract : Reconstructed human epidermis models are used as epidermis alternatives in skin research studies. It is necessary to provide molecular and functional characterization in order to assess these models. Our aim is to establish a link between the barrier function and the structure and composition of the stratum corneum using several complementary techniques. The following three studies were performed on reconstructed human epidermis during the keratinocyte differentiation process: (i) caffeine percutaneous penetration kinetics, (ii) epidermis thickness measurement, stratum corneum formation and lipid organization by Raman microspectroscopy and (iii) lipid composition evolution by liquid chromatography coupled to high-resolution mass spectrometry. The results demonstrated that the caffeine penetration decreased along the differentiation process. Raman in-depth images demonstrated an increase in stratum corneum and RHE thickness accompanied by the evolution of lipid organization. Lipid analysis showed an increase of the ceramide amount and an inverse relationship between ceramide and its precursor levels during the differentiation process. Different behaviors between several ceramide subclasses are highlighted and they relied on the corresponding differentiation stages. The generation of the most important ceramides for the barrier function is closely followed. A period shift between lipid generation and their organization was found. Our analytical data allowed identifying the following 3 groups of maturation days: before day 15, between days 15 and 19, and after day 19. The chemical and physiological states of the barrier function for each group are described thanks to a multimodal approach.